Clinical Supervision Instrument Development for Junior High School Teacher Based on Android - Lele, David Moto; Setiawan, Deni; Sulhadi, Sulhadi (Universitas Negeri Semarang, 2018)
The instruments currently used are still paper and pencil based. This development research aims to produce a clinical supervision instrument for android and junior high school teachers are valid and reliable. Data collection was done by interview and observation. Content validity was obtained through 4 expert judgments, analyzed using Aiken's V formula. The construct validity was analyzed by Exploratory Factor Analysis (EFA) and Intraclass Correlation Coefficient (ICC), and reliability with Alpha Cronbach with the help of IBM SPSS 24.0 software. The results showed that the validity value of all instruments in the preparation stage until the closing stage obtained a score> 0.5. The result of field test shows that there are some statement items that are in valid criteria with value of Factor Factor> 0, 5. Aspects with valid statement items include Preparation stages with 5 statements and Alpha Cronbach values ​​obtained at 0.640, Learning Activity stages with 23 statements and Alpha Cronbach values ​​obtained by 0.962, and Closing stages with 4 statements and Alpha Cronbach values ​​obtained at 0.680. Based on the results of the study, it was found that supervisors and teachers were very appreciative with the instrument of android based clinical supervision and the supervisor felt easier to conduct clinical supervision activities to the subject teachers. The benefits of this research are supervisors can use the instrument in carrying out clinical supervision with practical, easy and valid while for teachers can be used as a reference in preparing learning activities.